Siapa Konsumen Kita? : Analisis Perubahan Konsumen Di Era â€Ekonomi Baruâ€ - Adhikara, C. T. (Bina Nusantara University, 2005)
Economy has shifted into a new space. Itâ€™s often called New Economy or DigitalÂ Economy or Internet Economy. The characteristic of New Economy is signed byÂ technology application using internet in every sector, limitless of trade time and space.Speed is an important element for everything. It also affects consumer. Who is companyâ€™sÂ real consumer in this New Economy?Â